Hubungan antara ekspresi c-MET dengan derajat diferensiasi histologi dan tingkat kedalaman invasi pada infiltrating urothelial carcinoma kandung kemih di RSUP Sanglah, Bali, Indonesia - Kadek Agus Suhardinatha Putra; I Gusti Ayu Sri Mahendra Dewi; Herman Saputra; Ni Wayan Winarti; Anak Agung Ayu Ngurah Susraini; Ni Putu Ekawati; I Made Muliarta (DiscoverSys Inc., 2021)
Background: c-MET is a tyrosine kinase receptor that binds specifically to its ligand, namely hepatocyte growth factor (HGF). c-MET signaling deviations play a role in the progressivity of a wide variety of malignancies including bladder cancer. This study aims to determine the relationship between c-MET expression with the histological differentiation and depth of invasion in infiltrating urothelial carcinoma of bladder.Methods: This study was a cross-sectional analytical study with 42 sample sizes. The samples were taken from a paraffin block of patients with infiltrating urothelial carcinoma of the bladder, that has performed resection and histopathological examination who were examined at the Anatomical Pathology Laboratory of Sanglah Hospital Denpasar from 2015-2020. The c-MET expression was examined by immunohistochemical staining of c-MET and evaluated using the H-score method. Data were analyzed using SPSS version 20 for Windows.Results: Fisher's Exact test showed a statistically significant association between c-MET expression and the histological differentiation grade (p = 0.000). There was also a significant association between c-MET expression and depth of invasion with the Chi-Square test (p = 0.016), the Prevalence Ratio (PR) was 2.0 (95% CI = 1.2-3.6).Conclusion: In conclusion, there is an association between c-MET expression with the histological differentiation grade and depth of invasion in the infiltrating urothelial carcinoma of bladder. High c-MET expression had twice the risk of developing advanced invasion. Latar Belakang: c-MET merupakan reseptor tirosin kinase yang berikatan secara spesifik dengan ligannya, yaitu faktor pertumbuhan hepatosit (HGF). Penyimpangan c-MET signaling diketahui berperan dalam agresivitas berbagai macam keganasan termasuk kanker kandung kemih. Penelitian ini bertujuan untuk mengetahui hubungan antara ekspresi c-MET dengan derajat diferensiasi histologi dan tingkat kedalaman invasi pada infiltrating urothelial carcinoma kandung kemih.Metode: Penelitian ini merupakan studi analitik potong lintang dengan besar sampel adalah 42, yang berasal dari blok parafin penderita infiltrating urothelial carcinoma kandung kemih yang diperiksa histopatologi di Laboratorium Patologi Anatomi RSUP Sanglah Denpasar dari 2015-2020. Ekspresi c-MET diperiksa dengan pengecatan imunohistokimia c-MET dan dievaluasi menggunakan metode H-score. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Uji Fisher’s Exact menunjukkan hubungan yang bermakna secara statistik antara ekspresi c-MET dengan derajat diferensiasi histologi (p=0,000). Didapatkan juga hubungan yang bermakna antara ekspresi c-MET dengan tingkat kedalaman invasi dengan uji Chi-Square (p=0,016), prevalence ratio 2,0 (IK 95%=1,2-3,6).Kesimpulan: Sebagai simpulan terdapat hubungan antara ekspresi c-MET dengan derajat diferensiasi histologi dan tingkat kedalaman invasi pada infiltrating urothelial carcinoma kandung kemih. Ekspresi c-MET tinggi memiliki risiko dua kali lebih besar mengalami invasi lanjut. c-MET diharapkan dapat menjadi faktor prognostik yang bermanfaat dalam penatalaksanaan infiltrating urothelial carcinoma kandung kemih.